2022
DOI: 10.1080/10669817.2022.2148048
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral arteries do not experience tensile force during manual cervical spine manipulation applied to human cadavers

Abstract: Background: The vertebral artery (VA) may be stretched and subsequently damaged during manual cervical spine manipulation. The objective of this study was to measure VA length changes that occur during cervical spine manipulation and to compare these to the VA failure length. Methods: Piezoelectric ultrasound crystals were implanted along the length of the VA (C1 to C7) and were used to measure length changes during cervical spine manipulation of seven un-embalmed, post-rigor human cadavers. Arteries were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 185 publications
0
5
0
Order By: Relevance
“… 17 18 Furthermore, recent biomechanical studies report that head angular displacements and vertebral artery length changes are small during cervical spine manipulation thrusts 19 and that the vertebral artery does not experience longitudinal force during cervical spine manipulation. 20 Despite this literature, the serious nature of such events that are temporally associated with cervical spine manipulation makes it imperative that the circumstances surrounding such events are reported transparently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 18 Furthermore, recent biomechanical studies report that head angular displacements and vertebral artery length changes are small during cervical spine manipulation thrusts 19 and that the vertebral artery does not experience longitudinal force during cervical spine manipulation. 20 Despite this literature, the serious nature of such events that are temporally associated with cervical spine manipulation makes it imperative that the circumstances surrounding such events are reported transparently.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several large population-based studies have reported that there is no difference in risk of cervical artery dissection following visits to a chiropractor compared with those occurring following a visit to a primary care provider15 16 or, in those who received cervical spinal manipulation compared with matched controls 17 18. Furthermore, recent biomechanical studies report that head angular displacements and vertebral artery length changes are small during cervical spine manipulation thrusts19 and that the vertebral artery does not experience longitudinal force during cervical spine manipulation 20. Despite this literature, the serious nature of such events that are temporally associated with cervical spine manipulation makes it imperative that the circumstances surrounding such events are reported transparently.…”
Section: Introductionmentioning
confidence: 99%
“…A 2023 study concluded that CSM exerts no stretch on the vertebral artery, it simply elongates it [ 53 ]. In this case, it may be that any neck movement that elongates the vertebral artery more than CSM is a more probable alternative explanation.…”
Section: Reviewmentioning
confidence: 99%
“…Research does not support a causal association between cervical spine manipulation (CSM) and CAD. CSM causes little or no strain on the cervical arteries [ 2 , 3 ]. In a statement from the American Heart Association and American Stroke Association, Biller et al [ 4 ] found that biomechanical evidence is insufficient to establish the claim that CSM causes CAD and recommended that practitioners should strongly consider CAD as a presenting symptom prior to CSM.…”
Section: Introductionmentioning
confidence: 99%